Molecular Study of Mastitis Susceptibility in Human - Rawaa K. Judi (Journal of Global Pharma Technology, 2018)
Total of (260) clinical samples of blood and milk were collected from women, (160) sample from patients suffering from mastitis (80 samples from blood and 80 samples from milk), and (100) samples as control. Clinical samples were collected from mastitis women who visit the breast cancer consultant clinic in AL-Hilla Teaching Hospital at Babylon Provinces and Private Clinics. The period of samples collection were extended from October (2017) to January (2018). The mean of complement component 5a (C5a) levels in milk of women infected with mastitis was higher (250.9±15.8pg/ml) than the healthy ones (121.55±11.02pg/ml). The level of IL-6 and TLR2 concentrations in serum were measured in women mastitis cases as well as in the control groups by using ELISA technique. The mean of the serum levels of IL-6 in women infected with mastitis was higher (404.73±52.92 pg/ml) than the healthy ones (198.37±28.66 pg/ml). The mean of the serum levels of TLR2 in women infected with mastitis was higher (147.74±27.11pg/ml) than the control groups (83.36±8.58pg/ml). Genotyping of TLR2 polymorphisms was carried out by using Restriction fragment length polymorphism-Polymerase Chain Reaction (RFLP-PCR) technique. The polymorphisms in the single nucleotide for human TLR2 (Arg753Gln) gene polymorphism was detected in mastitis cases and the control groups, and the association between these polymorphisms with host susceptibility to mastitis was also determined. The results showed there was no differences between mastitis patients and control groups for alleles frequencies regarding Human TLR2 (Arg753Gln) polymorphism. However, that there were statistically significant difference in the frequency of TLR2 (Arg753Gln) genotype between patients with mastitis and control groups (P<0.05). Women with GA heterozygous genotype was overrepresented among the mastitis patients 22(50%) than in the controls 12(27.3%), suggesting an association with mastitis susceptibility; whereas the GG 20(45.5%) and AA 12(27.3%) genotype was more common in healthy subjects, than in mastitis patients 15 (34.1%) for GG and 7 (15.9%) for AA, suggesting a protective association with mastitis. The G and A alleles frequencies did not statistical difference as it was reported in Human TLR2 (Arg753Gln) between mastitis cases and control groups, the G allele frequency was 52(59 %) in the mastitis patients and same frequency in the control individuals, whereas A allele frequency was 36(41%) in the mastitis patients and in the control individuals. Keywords: Mastitis, Gene polymorphism, Complement component, RFLP-PCR.